Structural reforms in the EU: Policy prescriptions to boost productivity - Angana Banerji; Era Dabla-Norris; Minsuk Kim; Aleksandra Zdzienicka; Werner Roeger; Janos Varga; Jan in 't Veld; John Hassler; Dan Andrews (Intereconomics, 2015)
Productivity-enhancing structural reforms are crucial to the economic prospects of the EU. Indeed, such reforms are even more urgent in the current environment in which many economies are reaching the limits of the policy support they can provide to shore up demand. Moreover, even as some of the crisis-related effects fade, demographic headwinds loom, further strengthening the case for boosting productivity. The key question is how to identify, prioritise and calibrate the reforms that best suit each country's situation. This Forum examines specifi c barriers to enhanced productivity within the EU and puts forth policy proposals to offset the secular slowdown apparent in advanced economies and take better advantage of the EU's vast economic potential.
Keywords: 330; EU-Regionalpolitik; Produktivitätsentwicklung; EU-Staaten